Vasectomy: a study of attitudes, beliefs, knowledge and practices among literate men in Punjab, India - Sood, Aditya; Pahwa, Parika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Government launched the family planning program in India almost six decades back; further to that cause, it introduced non scalpel vasectomy to the public in 1992 aimed at male sterilization but despite of all the monetary incentives, IEC & BCC campaigns and increase in literacy rate, vasectomy still accounts for only 1 percent of all the family planning methods used across the nation. In Punjab, the coverage is just 0.6% and therefore this study was conducted to understand the attitude, knowledge, beliefs and myths amongst the participants in relation with vasectomy. Methods: A cross sectional descriptive study was carried out in three districts of Punjab. Literate married and unmarried men of age group 18-60 years with education qualification above 10th standard were included in the study. A total of 225 males, 75 from each district irrespective of caste, religion or socioeconomic status were selected by random sampling method. Results: 70% respondents had heard about vasectomy. 42% accepted it as a male contraceptive method but only 11% said that they would like to undergo the procedure in future. The primary reason cited for not undergoing vasectomy was that 53% men believed that tubectomy was a simpler procedure therefore their partners should undergo sterilization instead. 52% feared failure of the procedure and the bad name it would bring to the family; if partner gets pregnant. Conclusions: Government’s IEC and BCC activities should focus more on addressing the myths and fears of men; related to vasectomy.